2009
DOI: 10.1097/mlr.0b013e31817e18d1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Smoking Reduction Program

Abstract: In the absence of nicotine replacement therapy, the long-term effects of this smoking reduction intervention seem modest and nonsignificant. Future research is indicated to enhance intervention effects and conduct more comprehensive economic analyses of program variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 18 publications
2
55
1
1
Order By: Relevance
“…One was a randomized trial and included a usual care comparison group (29). Though QAs were not reported, the study found that reduction in CPD did not significantly increase point-prevalence abstinence (29). Thus, more research is needed to determine if reduction counseling without NRT increases QAs and abstinence in smokers who are not ready to quit.…”
Section: Introductionmentioning
confidence: 99%
“…One was a randomized trial and included a usual care comparison group (29). Though QAs were not reported, the study found that reduction in CPD did not significantly increase point-prevalence abstinence (29). Thus, more research is needed to determine if reduction counseling without NRT increases QAs and abstinence in smokers who are not ready to quit.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study included in the review, a smoking cessation study, 87 identified a social ecological approach as the theoretical background for intervention activities, limiting our ability to draw conclusions regarding the usefulness of this theory in promoting maintenance of health behaviors. The paucity of studies referencing an ecological framework was somewhat surprising given the increased focus on using ecological approaches to promote behavior change in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, including Wu and colleagues' recent finding, two of three trials found reduction interventions without medication for smokers not ready to quit increases cessation in comparison to no treatment [5,7,8]. Whether this is due to the reduction intervention, advice to quit, or both, and whether this is due to increasing QAs or quit success remains unclear.…”
mentioning
confidence: 99%
“…One explanation for this difference is that reducing CPD could be effective by increasing motivation to quit [11] and thus less impactful for those already motivated to quit. Another explanation is that, among smokers who intend to quit now, reducing CPD delays quitting which could decrease motivation to quit [13].In summary, including Wu and colleagues' recent finding, two of three trials found reduction interventions without medication for smokers not ready to quit increases cessation in comparison to no treatment [5,7,8]. Whether this is due to the reduction intervention, advice to quit, or both, and whether this is due to increasing QAs or quit success remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation